1997
DOI: 10.1136/jmg.34.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Paternal uniparental disomy for chromosome 6 causes transient neonatal diabetes.

Abstract: We report an infant with intrauterine growth retardation and transient neonatal diabetes who has paternal uniparental disomy for chromosome 6. The infant was not dysmorphic and had no congenital anomalies. To our knowledge, this is the third case of paternal uniparental disomy occurring in an infant with transient neonatal diabetes, thus confirming the association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 9 publications
2
14
0
1
Order By: Relevance
“…10 The association between TNDM and paternal UPD6 has been observed in at least six independent cases in various ethnic groups. 4,5 These recent reports and our observation are in favour of the involvement of imprinted gene(s) on the chromosome region 6q23-q24. 6 Chromosome 6 paternal isodisomy is found in approximately 20-30% of patients with TNDM.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…10 The association between TNDM and paternal UPD6 has been observed in at least six independent cases in various ethnic groups. 4,5 These recent reports and our observation are in favour of the involvement of imprinted gene(s) on the chromosome region 6q23-q24. 6 Chromosome 6 paternal isodisomy is found in approximately 20-30% of patients with TNDM.…”
Section: Discussionsupporting
confidence: 64%
“…Chromosome 6 duplications, 2,3 and paternal uniparental disomy of chromosome 6 (UPD6), isodisomy, have been described in patients with TNDM. 4,5 A candidate region on 6q23-q24 has been identified with an imprinted gene thought to be involved in the maturation of pancreatic beta-cells. 6 We report two further cases of TNDM with paternal UPD6, with different growth patterns and clinical abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on cases with paternal isodisomy of chromosome 6 have demonstrated strong evidence that an imprinted gene linked to the HLA region is implicated in a mechanism of diabetes mellitus and an autoimmune disorder (Abramowicz et al 1994;Whiteford et al 1997;Arthur et al 1997;Temple et al 1995). This finding indicates that deregulation of genomic imprinting at the HLA-DQ region should have profound effects on pancreatic beta cell function and the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 5 further cases with TND and paternal UPD6 have since been reported in the literature (8)(9)(10)(11)(12), and another involved a child with diabetes who died at the age of 16 days (13). The association is now firmly established, although 2 cases of paternal UPD6 have been reported in older patients with no early history of TND, which cannot yet be explained (14,15).…”
mentioning
confidence: 99%